Peningkatan Pengetahuan Masyarakat Tentang Tuberkulosis dan Bahaya Merokok Melalui Edukasi Kesehatan di Desa Krajan Kecamatan Gatak Kabupaten Sukoharjo - Assyifa Bani Alleia; Rizalta Risqi Ananda; Tsania Nurul Izzah; Desslyta Ayu Rizqya Putri C; Salsabila Bil Izzati; Syahira Fathina Rahmadewi; EM Sutrisna (Universitas Pahlawan Tuanku Tambusai, 2026)
Tuberculosis (TB) is a contagious infectious disease that remains a public health problem in Indonesia. Risk factors such as low public awareness, unhealthy home environments, and exposure to cigarette smoke can increase the risk of TB transmission. This activity aims to increase public awareness of tuberculosis and the dangers of smoking through screening and health education activities in Krajan Village, Gatak District, Sukoharjo Regency. The method used was a descriptive observational approach through door-to-door activities with six respondents. The activity was carried out through interviews using questionnaires, administering pretests and posttests, observing home environmental conditions, and health education using posters. The results showed that most respondents were not active smokers, but were passive smokers because they lived with family members who smoked. In addition, one respondent was found to be a former active smoker with a long-term smoking history. Public knowledge about TB was still relatively low before the education was provided, especially regarding transmission and prevention of the disease. After the health education, most respondents experienced an increase in posttest scores, indicating an increased understanding of TB and the dangers of smoking. Other risk factors identified were inadequate home ventilation, advanced age, and the presence of comorbidities in several respondents. Direct health education activities are considered effective in increasing public knowledge because they allow for two-way interaction between educators and residents. These activities are expected to raise public awareness of the importance of early TB detection, adopt healthy lifestyles, and reduce exposure to cigarette smoke in the family and community.